Quasi-static indentation of reinforced thermoplastic pipe (RTP) - Bakar, M.A.A. (Penerbit UTHM, 2020)
Reinforced Thermoplastic Pipe (RTP) is a type of flexible composite pipe that extensively being used in Oil & Gas Industry, it possesses a huge potential as a replacement of commercial carbon steel pipe, especially in high corrosive environment. However, the commercial design of RTP does not consider the effect of lateral load from external interference. In the quasi-static indentation test conducted, the maximum local deformation recorded is 62.5 mm at lateral load of 16.1 kN. However, the effect of elastic rebound reduced 92 of the maximum deformation to produce a permanent dent of 5 mm, it can be hypothesized that a dent in RTP might not represent the actual degradation of RTP. This paper discussed the procedure, response and degradation of RTP when subjected to lateral compressive load in a Quasi-static environment. Â© Universiti Tun Hussein Onn Malaysia Publisherâs Office.